2013
DOI: 10.1097/ncc.0b013e31826c96d9
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Receiving Palliative Treatment

Abstract: The attention of health professionals must be directed at recognizing and enhancing patients' ways of seeking knowledge to help them make sense of receiving palliative treatment. Person-centered activities need to be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
(30 reference statements)
1
16
0
Order By: Relevance
“…The present study is a secondary aim of a larger project about information provision among people receiving palliative cancer care [28,29,31] where the fieldwork was informed by life-world phenomenology [12,32]. The analysis was performed according to hermeneutic interpretive principles out of Ricoeur’s theory of interpretation in three inter-related steps: naïve reading, structural analysis and interpreted whole [33-35].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study is a secondary aim of a larger project about information provision among people receiving palliative cancer care [28,29,31] where the fieldwork was informed by life-world phenomenology [12,32]. The analysis was performed according to hermeneutic interpretive principles out of Ricoeur’s theory of interpretation in three inter-related steps: naïve reading, structural analysis and interpreted whole [33-35].…”
Section: Methodsmentioning
confidence: 99%
“…All of them had children but only three had children at home, one had deceased children, and three were widowed with adult children. The participants had a range of occupational backgrounds, and differed in their employment status (8 were retired, 3 on sick leave and 3 worked part time and part-time on sick leave) and the majority had a history of cancer in the family (for more details, see [28]).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of a study conducted in Germany also showed that the delivery of palliative care to cancer patients is the ongoing process of understanding patients and making sense of their conditions. On the other hand, an essential prerequisite to empathy is active listening which significantly reduces patients' stress (28). As an empathetic behavior, our participants strived to place themselves in patients' shoes or considered them as their own family members.…”
Section: Discussionmentioning
confidence: 99%